Modelo de gestión para la aplicación de herramientas Lean Manufacturing para la mejora de la productividad en una empresa de confección de ropa antiflama de Lima - Perú - Ortiz Porras, Jorge (2022)
This research focuses on the analysis of the manufacturing process and standard times of a company that manufactures flame-resistant clothing in Lima, Peru, to elaborate a management model based on Lean Manufacturing tools aimed at improving the company’s productivity and providing a model that can be implemented in similar environments. The first step was to identify the problems and, upon observation, a continuous improvement plan was drawn up following the DMAIC methodology (define, measure, analyze, improve and control), which focuses on the incremental improvement of processes. Following the implementation of the 5S (that creates a continuous process of improvement of the work environment and helps to make problems visible), learning instructions, a time study and a total maintenance plan, there was a 20% increase in man-hour productivity. The model was also subjected to expert judgment and obtained an Aiken V validation value of 100%, indicating that the model is effective in improving productivity in clothing companies.